The activity of polyclonal IgY derived from Aggregatibacter actinomycetemcomitans and Porphyromonas gingivalis in inhibiting colonization of Fusobacterium nucleatum and Streptococcus sanguinis - Oktaviani Suci Lestari; Rini Devijanti Ridwan; Tuti Kusumaningsih; S. Sidarningsih (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2019)
Background: Fusobacterium nucleatum (F. nucleatum) and Streptococcus sanguinis (S. sanguinis) play a role in dental plaque formation which leads to periodontitis. Immunoglobulin Y (IgY) is present in both serum and egg yolk and can bind to the surface components of bacteria. F. nucleatum and S. sanguinis feature the same type of IV pili as Aggregatibacter actinomycetemcomitans (A. actinomycetemcomitans). Saliva binding protein (SsaB) in S. sanguinis is a FimA homolog. FimA constitutes a surface element of Porphyromonas gingivalis (P. gingivalis). F. nucleatum and P. gingivalis possess the same outer membrane protein (OMP) molecular mass. Purpose: The study aimed to determine the activity of A. actinomycetemcomitans and P. gingivalis polyclonal IgY present in serum and egg yolk that can inhibit colonization of F. nucleatum and S. sanguinis. Methods: IgY samples were diluted with phosphate buffer saline (PBS). Several holes were made in the nutrient medium with 10 μl antigen (F. nucleatum/S. sanguinis) being inserted into the center hole. 10 μl PBS, 1:1, 1:2, 1:4, 1:8, 1:16 A. actinomycetemcomitans or P. gingivalis polyclonal IgY were subsequently introduced into the surrounding holes. The results of incubation at 37°C were observed after 24-48 hours. Kruskal Wallis and MannWhitney tests were administered to analyse the data. Results: A. actinomycetemcomitans and P. gingivalis polyclonal IgY groups in serum showed a precipitation line at dilution ratios of 1:1 and 1:2, whereas in egg yolk this occurred only at a 1:1 dilution ratio with F. nucleatum and S. sanguinis bacteria in this study. No significant differences were evident between each dilution (p>0.05) and none existed between serum and egg yolk (p>0.05). Conclusion: IgY polyclonal of A. actinomycetemcomitans and P. gingivalis in both serum and egg yolk initiate activities that can inhibit colonization of F. nucleatum and S. sanguinis.